Ultrasound-Guided Genicular Nerve Thermal Radiofrequency Ablation for Chronic Knee Pain - Joshua Wong; Nicholas Bremer; Paul D. Weyker; Christopher A. J. Webb (Case Reports in Anesthesiology)
Osteoarthritis (OA) of the knee is one of the most common joint diseases affecting adults in the United States. For elderly patients with multiple medical comorbidities who do not wish to undergo total knee arthroplasty (TKA), lifestyle modification, pharmacologic management, and injections are the mainstay of therapy. Previously, pain management interventions were limited to intra-articular joint injections and viscosupplementation with hyaluronic acid. Fluoroscopic-guided techniques for radiofrequency ablation (RFA) of the genicular nerves have been previously described and a recent cadaveric study suggests that ultrasound-guided genicular nerve blocks can be performed accurately. We performed an ultrasound-guided radiofrequency ablation of the genicular nerves in 88-year-old woman who had deferred surgical management given her age. Following successful ultrasound guided diagnostic genicular nerve blocks, she proceeded to RFA using the same ultrasound guided technique. The procedure resulted in significant pain relief and improvement in overall function for greater than 6 months. The use of ultrasound provides a relatively rapid and noninvasive method to directly visualize genicular nerves and surrounding vasculature. Our case suggests that, for genicular nerve blockade and RFA, ultrasound may be a useful alternative to fluoroscopy. Not only did the procedure result in significant pain relief that has persisted for greater than 6 months but also more importantly her function status and quality of life were improved.